2010
DOI: 10.1007/978-1-60761-913-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up of Protein Purification: Downstream Processing Issues

Abstract: Large-scale chromatography operations continue to occupy a key position in the overall strategy for the downstream processing and purification of protein products for therapeutic use. Increasing product titres from mammalian cell culture has resulted in a trend to identify ways of improving the economics of product recovery and purification processes. In commercial manufacturing, a requirement exists to increase the scale of the chromatography operations, which are typically developed and optimised in small-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Thus, downstream processing has become a bottleneck in biotherapeutic production 35 . Efforts to alleviate this have mostly focused on innovations in process design to improve downstream processing capacity, speed, and economics 36,37 . It has also been suggested that cell line engineering could be used to reduce or remove problematic NATURE COMMUNICATIONS | https://doi.org/10.1038/s41467-020-15866-w ARTICLE HCPs, lessening the need for additional purification steps 6,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, downstream processing has become a bottleneck in biotherapeutic production 35 . Efforts to alleviate this have mostly focused on innovations in process design to improve downstream processing capacity, speed, and economics 36,37 . It has also been suggested that cell line engineering could be used to reduce or remove problematic NATURE COMMUNICATIONS | https://doi.org/10.1038/s41467-020-15866-w ARTICLE HCPs, lessening the need for additional purification steps 6,38 .…”
Section: Discussionmentioning
confidence: 99%
“…A detailed overview about important chromatographic and non-chromatographic issues which have to be considered during the development and also for choosing the fi xed parameters for a chromatographic step is given in the review of Milne [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…For an overview about further important aspects for the development of a downstream procedure for protein purifi cation the reader is referred to Milne [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For clarification, crude extracts can be filtered or centrifuged to separate debris from any soluble products into the supernatant fraction. Capture and purification occurs mostly for protein products used for human therapeutic, cosmetic, or nutraceutical purposes (Milne 2017). Chromatographic operations and/or precipitation steps are commonly used to purify and concentrate proteins.…”
Section: Proteins Carbohydrates Lipids Pigmentsmentioning
confidence: 99%